Functional analysis of Arabidopsis V-ATPase subunit VHA-E isoforms - Dettmer, Jan; Liu, Tzu-Yin; Schumacher, Karin (European journal of cell biology, 2010)
Acidification of endomembrane compartments by the vacuolar H+-ATPase (V-ATPase) is an important mechanism to generate microenvironments suitable for various cellular functions. Differential assembly of subunit isoforms provides the potential to flexibly adapt the proton-pumping V-ATPase complex to changing physiological conditions and cell type-specific requirements. In Arabidopsis, the regulatory V-ATPase subunit E (VHA-E) is encoded by three genes with distinct expression patterns. We show here that VHA-E2, which belongs to a clade of pollen-specific VHA-E isoforms present in all higher plants, has a specialized but non-essential function during gametophyte development. Similarly, loss of the epidermis-specific isoform VHA-E3, which we show here to be transcriptionally regulated by the phytohormone jasmonic acid, does not cause obvious phenotypic changes. Furthermore, when expressed ubiquitously, VHA-E3, in contrast to VHA-E2, is able to complement loss of the essential subunit VHA-E1 indicating different degrees of functional specialization among the Arabidopsis VHA-E isoforms.